The World Bank Legal Review, Volume 7. Financing and Implementing the Post-2015 Development Agenda : The Role of Law and Justice Systems - Fariello, Frank (2016)
The newly adopted post-2015 development agenda is centered on 17 sustainable development goals to be reached by 2030. This volume of the World Bank Legal Review looks at how law and justice systems can support the financing and implementation of these goals, including the role of the rule of law and economic and social rights. The contributors, including legal scholars, development practitioners, and financial experts, analyze the goals, explore ways in which they can be achieved, and examine ways that recent relevant law and justice programs have worked. A wide array of topics are covered, from the legal aspects of collecting and monitoring vital data, to improving legal identity programs, to creating innovative health care regulation, to legal and judicial reform, to providing private sector–financing of public education projects to the provision of global public goods. Additionally, a special section on Europe looks at financial crisis management, enforcement of court decisions and the workings of the European Court of Justice. The opportunities and challenges of the 2030 agenda are many. This volume looks at both from multiple perspectives, demonstrating how sustainable development can go forward in a way in which everyone benefits.